A systematic review to determine the quality and need for support and education received on death and dying for critical care nurses. - Ryan, Lucy (2012)
Aim: To what extent are nurses in intensive care prepared and supported for the issues they face when providing end-of-life care for patients in a critical care environment? Background: Futile provision of care in ICU is a major cause of unnecessary stress and burnout for critical care nurses. Integration of palliative care skills into an already technologically advanced ICU needs to be standardised in order to prepare nurses for the emotional labour required of them to elicit high quality end-of-life care. Recognition of nurses in the decision-making process associated with withdrawal of treatment should be better recognised, and support and education should be further enhanced to maintain nurses’ integral role in end-of-life provisions. Methodology/Principle Findings: Literature found using databases CINAHL, MEDLINE (OVID), BNI and Web of Science along with cited references were used in the production of this study. Only 10 articles matched with the detailed inclusion/exclusion criterion, due to the specificity of using only UK based research. Adaptations of the CASP framework provided a tool for critiquing each study, as well as data extraction to formulate six themes. The strong link these had whilst presenting the findings show the importance of managing grief of critical care nurses through appropriate support and education. Further discussion highlighted what can be learnt from international initiatives and how theoretical base should be applied when constructing accessible forms of both support and training for critical care nurses. Conclusions/Significance: The difficulties this systematic review has faced lay simply with the lack of research devoted solely to on-going learning and support mechanisms for nurses providing end-of-life care in the ICU. Not all articles used were of empirical origin and so critical appraisal was perhaps not as concise as would be preferred. Despite this, valuable lessons have been learnt, and the requirement for further empirical research in this area has been justified. What this paper adds: This study provides a structured review of the literature available that explores the concept of grief and emotional labour with need for improved methods of support and education for nurses in ICU. End-of-life care is an essential role as a nurse, and high quality standards should be available throughout all ICU settings in the UK. This study sets out what previous literature suggests and should be used as grounding for the production of effective research in the future.